Impact of gender, depression severity and type of depressive episode on efficacy and safety of escitalopram: an observational study on major depressive disorder patients in southern India - Tatiyana Mandal; Laxminarayana Kurady Bairy; Podila Satya Venkata Narasimha Sharma; Vijaya Lakshmi Valaparla (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2021)
Abstract Background Antidepressant response is a complex trait influenced by clinical, demographic and genetic factors. Objectives To explore the influences of baseline depression severity, gender and type of depressive episode on efficacy and safety of escitalopram (10–20 mg/day) in South Indian patients with major depressive disorder (MDD). Methods The study was conducted on 18–65-year-old patients (n = 151) suffering from a first or recurrent episode of MDD with a 17-item Hamilton Depression Rating Scale (HDRS-17) score of ≥ 18 at baseline. Efficacy assessments were done using HDRS-17, Montgomery-Asberg Depression Rating Scale (MADRS), and Clinical Global Impression (CGI) at baseline and weeks 4, 8 and 12. Patients were monitored for adverse drug reactions (ADRs). Clinical outcomes were compared among various groups based on gender, type of depressive episode (first or recurrent episode) and baseline HDRS-17 scores (moderate depression—score between 17 and 23; severe depression—score ≥ 24). Results Among the 148 subjects who completed the 12-week study, 43.9% and 42.6% achieved response and remission, respectively. The decline in HDRS-17 and MADRS scores from baseline was significant (p value < 0.05) at all follow-up visits and a similar pattern was seen with CGI. Efficacy outcomes were better in the moderate baseline depression group compared with severe depression. There were no associations of efficacy with gender and type of depressive episode. A total of 247 adverse drug reactions (ADR) were reported and 119 (80.41%) subjects experienced at least one ADR during the study period. No serious ADR was reported. Male patients experienced more ADRs compared with females. The safety profile of escitalopram was similar across various groups based on baseline depression severity and type of depressive episode. Conclusion The study revealed that escitalopram is efficacious in south Indian MDD patients with a favourable safety profile. The efficacy was influenced by baseline depression severity whereas more ADRs were reported by male patients.